Internalisasi Nilai-Nilai Religius dan Kemandirian Mahasantri Putri melalui Kegiatan Ma’had di Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep - Muruatul Afifah; Nurul Qomariyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The problem raised in this study is how the process of internalizing religious values ​​and independence of female students through ma'had activities at IDIA Prenduan and what are the implications of internalizing religious values ​​and independence of female students through ma'had activities at IDIA Prenduan. This study uses a qualitative descriptive approach with a case study type. The methods used are interview, observation, and documentation methods. For data analysis, the researcher used the Miles, Hubberman and Saldana model, through data collection, data condensation, data presentation and drawing conclusions. From the validity of the data, the researcher used triangulation with source triangulation. The results of this study indicate that the process of internalizing religious values ​​and independence of female students through ma'had activities at the Al-Amien Prenduan Islamic Boarding School Institute has 3 stages, namely (1) the value transformation stage, namely through lectures, istirham, dawn lectures, and tadarrus muwajjah. (2) the value transaction stage through dirosah sobahiyah, tahsinul qiro'ah, and muhadhoroh activities. (3) trans-internalization stage, namely the habituation of female students and enforcement of regulations. The implications of the internalization of religious values ​​and independence of female students through the ma'had activities at the Al-Amien Prenduan Islamic Education Institute are that female students have targets, planning, can appreciate time, and become mature.